A chromosomal level genome assembly of Nguni sheep, Ovis aries - Nesengani, L.T.; Tshilate, T.; Mdyogolo, S.; Smith, R.; Masebe, T.; Raphulu, T.; Moila, A.; Sharaf, A.; Muzemil, S.; Houaga, I.; Muigai, A.; Djikeng, Appolinaire; et al. (Nature Research, 2025)
Nguni sheep (Ovis aries) are indigenous to the Southern Africa region and common within the smallholder and poor resources farming systems. They are well adapted to different agroecological regions. However, limited genomic resources such as high-quality reference genomes have hindered our understanding of its adaptation and establishment of an effective breeding program. To address this, we assembled a chromosomal-level genome of Nguni sheep using a combination of PacBio HiFi reads and Omni-C reads. The genome size was estimated to be 2.9 Gb with a contig/scaffold N50 74 Mb and 99.6 Mb and a genome completeness of 96.1%, as estimated by the Benchmarking Universal Single-Copy Orthologs (BUSCO) program. The final genome encompassed a total of 25,926 protein-coding genes. The findings of this study provide a valuable genomic resource for understanding the adaptability of the Nguni sheep and the establishment of effective breeding programs.